Design of a gastrofloatable and gastroadhesive drug delivery system for narrow absorption window and low bioavailable drugs - Murphy, Caragh Synnøve (My University, 2011)
Electro-spinning of polymers is a unique technology which produces very fine fibres using electrostatic repulsive forces obtained from applying an electrical potential to a liquid. The resultant fibres have much smaller diameters in comparison with fibres obtained using different methods. Electro-spun fibres have found application in many and varied fields such as drug and gene delivery, tissue engineering, wound dressing, electronics, filtration as well as absorption and adsorption. This review will cover the various processing parameters which play a role in electro-spinning, including the applied voltage, solution flow rate, solution viscosity, solvents, solution conductivity, capillary-to-collector distances and the influence of surfactants. A main focus will be on the application of electro-spun fibres in drug delivery, where researchers have already investigated the use of these fibres in transdermal delivery systems, long-term implants and grafts. Different methods of drug incorporation will be discussed as well as numerous polymers which have been successfully utilised in this field, including cellulose acetate, poly(ε-caprolactone), poly(ethylene oxide), poly(vinyl alcohol), gelatin, poly(d,l-lactide-co-glycolide), poly(lactic acid), poly(l-lactic acid), polyurethane, poly(ethylene-co-vinyl acetate), poly(ethylene glycol), and poly(acrylic acid). Keywords: Electro-spinning, drug delivery, electrospun fibres, electrospun scaffolds, Parameters.